The impact of digitalisation on employment and productivity in the financial sector: A comparative analysis of information and communication technology usage of Central European and Baltic businesses - Arnold Tóth; Ramin Astanli; Erika Varga (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The article aims to examine the impact of digitisation on employment and productivity in the financial sector and provide a comparative analysis between the Central European and the Baltic countries as no study has yet compared these two regions in terms of digitalisation and information and communication technology (ICT) usage despite similar economic backgrounds. Research Design & Methods: To address this, we applied a two-pronged approach that combines a literature review with an empirical analysis of secondary data. We used multivariate analysis of variance (MANOVA) to estimate the simultaneous total effect of ICT use on employment and productivity and ordinary least squares (OLS) regression to examine the specific relationships identified by MANOVA. Findings: Central European countries generally exhibit higher levels of employment and productivity than their Baltic counterparts, highlighting regional differences in economic conditions and labour market dynamics. ICT has a major impact on productivity but is also associated with declining employment levels, which raises concerns about potential job displacement. Investments in the financial sector have a positive effect on employment, which highlights its crucial role in supporting employment growth. Implications & Recommendations: By implementing best practices and encouraging a culture of ongoing learning and innovation, the digital transformation of Central Europe and the Baltic countries can become smooth and successful. Regional comparative analysis further provides valuable contextual insights, highlighting the need for tailored policy interventions. Contribution & Value Added: The analysis shows that investments do not have a significant direct effect on productivity. Capital investment does not guarantee an increase in output, just emphasises the need for a strategic investment approach.
Keywords: G10; M15; O32; 330; digitalisation; employment; finance; ICT; productivity